Investigation of the effects of laparoscopic sleeve gastrectomy and laparoscopic one anastomosis gastric bypass on metabolic syndrome components - Vahit Mutlu; Mahmut Arif Yüksek; Bülent Koca; Gökhan Selçuk Özbalcı (BMC Surgery)
Abstract Background Obesity and accompanying comorbidities are serious diseases that impair the quality of life and even threaten human life. Today, the most effective method for providing sustainable weight loss in the treatment of obesity is Bariatric and Metabolic Surgery procedures. In our study, we aimed to compare the therapeutic effects of Laparoscopic Sleeve Gastrectomy (LSG) and One Anastomosis Gastric Bypass (OAGB) on metabolic syndrome components. We also planned to investigate the complications after bariatric and metabolic surgery, whether the patients had recurrent weight gain, and the short, medium and long-term effects. Methods Patients who underwent bariatric and metabolic surgery with the diagnosis of obesity between December 2012-January 2020 were retrospectively analyzed. 561 patients who were followed up at 3, 6 months, 1, 2 and 3 years after the operation were included in the study. The effects of bariatric and metabolic surgery on metabolic syndrome components were evaluated as partial and complete remission according to the status at the last follow-up. Statistical analysis were performed by SPSS 18. Results were reported as mean ± standard deviation. P < 0.05 was accepted as statistical significance. Results In 516 patients who underwent LSG and 45 patients who underwent OAGB, a decrease in BMI and an increase in EWL(%) values were observed at the 3rd month, 6th month, 1st year and 2nd year controls. In the 3rd year controls of patients who underwent LSG, recurrent weight gain was observed, therefore there was an increase in BMI and a decrease in EWL(%) values compared to the 2nd year. In patients who underwent OAGB, a decrease in BMI continued at the 3rd year, while an increase in EWL(%) values was observed. Thanks to both LSG and OAGB; a remission was achieved at the rates of DM, HT, HL/DL, OSAS, hypothyroidism in the early period. As the follow-up period extended, the rate of patients showing complete recovery decreased for DM(p = 0.0001). No change was observed during the follow-up period for other parameters. Conclusıon Therapeutic effects of LSG and OAGB on metabolic syndrome components have been demonstrated in our study. However, when DM remission and sustainable weight loss are evaluated, OAGB is more effective in the long term.